Reasons for Rejecting of Contraceptive Technologies: Case Study of Educated Women in Sri Lanka - Perera, B. Nishanthi (My University, 2012)
In many countries, contraceptive use is one of the most important proximate determinants which affect fertility through socio-economic factors. Increasing mean age at marriage and declining marital fertility were two main causes that contributed to fertility transition in Sri Lanka. From the beginning of the 1970s’, modern contraceptive technologies have made a significant contribution to the fertility decline in Sri Lanka. During 1995-2000, Sri Lanka has reported a Total Fertility Rate (TFR) of 1.9, indicating that Sri Lanka has reached below replacement level fertility. However, the latest Sri Lanka Demographic and Health Survey (SLDHS) shows that there is an upturn in TFR in Sri Lanka reporting a TFR of 2.3. The effectiveness of a contraceptive method mainly depends on quality of practice. Modern contraceptive technologies are more effective than traditional methods in preventing pregnancy. Although ever-married and currently married educated women in Sri Lanka have a good knowledge of modern contraceptive methods, the data suggests they are less likely to use them when compared to less educated women. Instead, they use traditional contraceptive methods. Therefore, it is important to explore the factors influencing the rejection of modern contraceptive methods among educated women in Sri Lanka. The main objective of this study is to examine the reasons for educated women in Sri Lanka rejecting or showing less interest in modern contraceptive technologies. The study mainly uses qualitative data gathered through in-depth interviews. In addition, quantitative data from the recent Sri Lanka Demographic and Health Survey (2006/7) was also used to explore the patterns and differences of contraceptive use among women in Sri Lanka. The qualitative research findings revealed that the key factors which contribute to the rejection of contraceptive technologies are fear of side effects, lack of time for using modern contraceptive methods, lesser frequency of sexual intercourse and misbeliefs regarding modern contraceptive methods. Since educated working women openly discuss their experiences and beliefs with other working colleagues, it is more likely that educated women spread misbeliefs on modern contraceptive methods, which will further decrease the level of use of modern methods. Therefore, the study has pointed out several policy implications such as introducing institutionalized awareness programmes on contraceptive technologies (in private and government sector) and strengthening the family planning counseling programmes which target educated women.